2018
DOI: 10.1159/000491526
|View full text |Cite
|
Sign up to set email alerts
|

MiR-137 Suppresses Triple-Negative Breast Cancer Stemness and Tumorigenesis by Perturbing BCL11A-DNMT1 Interaction

Abstract: Background/Aims: Triple negative breast cancer (TNBC) is resistant to conventional chemotherapy due to high proportions of cancer stem cells (CSCs). The aim of this study is to unravel the miR-137-mediated regulatory mechanism of B-cell lymphoma/leukemia 11A (BCL11A) in TNBC. Methods: A corhort of 34 TNBC tumor tissues and paired adjacent normal tissues, as well as 25 non-TNBC tumor tissues and paired adjacent normal tissues were collected post-operatively from patients with breast cancer. Q-PCR was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 35 publications
(55 reference statements)
2
35
0
Order By: Relevance
“…BCLL11A interacts with DNA methyltransferases 1 (DNMT1), which also contributes to CSCs' maintenance in various cancers, including breast cancer [68]. miR-137 also disturbs the BCL11A-DNMT1 interaction by suppressing BCL11A expression at both the mRNA and protein level [69]. As a result, TNBC development and cancer stemness are impaired.…”
Section: Mir-137mentioning
confidence: 99%
“…BCLL11A interacts with DNA methyltransferases 1 (DNMT1), which also contributes to CSCs' maintenance in various cancers, including breast cancer [68]. miR-137 also disturbs the BCL11A-DNMT1 interaction by suppressing BCL11A expression at both the mRNA and protein level [69]. As a result, TNBC development and cancer stemness are impaired.…”
Section: Mir-137mentioning
confidence: 99%
“…However, in tumour cells such as in TNBC, specific miRNAsare critical for tumorigenesis and development 10 . Although many studies have already confirmed that multiple core miRNAs can induce epithelial mesenchymal transition (EMT) 11 , stemness 12 , migration, and invasion 13 , thus, facilitating tumour cell growth and invasion, a more comprehensive study is still needed to investigate the miRNA regulatory network in TNBC.…”
mentioning
confidence: 99%
“…Among these candidates, miR-137 was fascinating in the present study because of its tumor-suppressive property in a lot of human cancers, such as breast cancer, non-small cell lung cancer and ovarian cancer. [28][29][30] MiR-137 was also reported to hamper CRC progression by suppression of cell proliferation, invasion and migration. [31][32][33] Additionally, miR-137 enhanced the chemosensitivity in ovarian cancer and colon cancer.…”
Section: Discussionmentioning
confidence: 99%